1995
DOI: 10.1523/jneurosci.15-09-06281.1995
|View full text |Cite
|
Sign up to set email alerts
|

Brain space for learned song in birds develops independently of song learning

Abstract: In numerous species of birds, individuals or species that sing larger numbers of song types have larger song control nuclei in their brains. The direction of the cause and effect relationship between the complexity of song behavior and brain space is unknown, however. The hypothesis that birds that learn large song repertoires develop large song nuclei was therefore tested with a songbird, the marsh wren (Cistothorus palustris). Males were hand-reared and tutored in the laboratory with either small (n = 8 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 11 publications
(28 reference statements)
6
69
0
Order By: Relevance
“…Burek et al (1991) showed that the total number of HVC neurons in zebra finches deafened early in ontogeny was no different from that seen in intact controls. In line with this, Brenowitz et al (1995) showed that marsh wrens (Cistothorus palustris) induced to learn large song repertoires had no more HVC neurons than those that, because of limited tutoring, had small repertoires. Our observations indicate that the number of HVC neurons present in adulthood is much the same in intact zebra finches that mastered a model as in those that, because of early deafness or syringeal denervation, were unable to imitate a model.…”
Section: Discussionmentioning
confidence: 55%
“…Burek et al (1991) showed that the total number of HVC neurons in zebra finches deafened early in ontogeny was no different from that seen in intact controls. In line with this, Brenowitz et al (1995) showed that marsh wrens (Cistothorus palustris) induced to learn large song repertoires had no more HVC neurons than those that, because of limited tutoring, had small repertoires. Our observations indicate that the number of HVC neurons present in adulthood is much the same in intact zebra finches that mastered a model as in those that, because of early deafness or syringeal denervation, were unable to imitate a model.…”
Section: Discussionmentioning
confidence: 55%
“…There are very few comparable experimental studies, except those on the American marsh wren Cistothorus palustris (Kroodsma & Canady 1985;Brenowitz et al 1995). These used a slightly different technique of tutoring males with tapes of varying song complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Following previous work with brown-headed cowbirds, we measured the Tel from the first slice in which Hp appeared to the last slice in which we measured Hp (Sherry et al, 1993). On sections in which the telencephalic hemispheres were joined with the diencephalon, prominent markers such as the occipito-mesencephalic tract and the anterior commissure were used to determine telencephalic boundaries (Brenowitz, Lent, & Kroodsma, 1995). The NRot boundaries are particularly clear in Nissl-stained sections ( Figure 1B).…”
Section: Histology and Morphometricsmentioning
confidence: 99%